Impact of Adenotonsillectomy on Homework Performance in Children With Obstructive Sleep-Disordered Breathing. (November 2022) - Wu, Derek; Au, Vivienne H.; Yang, Billy; Horne, Sylvia J.; Weedon, Jeremy; Bernstein, Michelle J.; Goldstein, Nira A.
Objective: As a first line treatment for pediatric obstructive sleep-disordered breathing (SDB), adenotonsillectomy (AT) has been shown to confer physiologic and neurocognitive benefits to a child. However, there is a scarcity of data on how homework performance is affected postoperatively. Our objective was to evaluate the impact of AT on homework performance in children with SDB. Methods: Children in grades 1 to 8 undergoing AT for SDB based on clinical criteria with or without preoperative polysomnography along with a control group of children undergoing surgery unrelated to the treatment of SDB were recruited. The primary outcome of interest was the differential change in homework performance between the study group and control at follow-up as measured by the validated Homework Performance Questionnaire (HPQ-P). Adjustments were made for demographics and Pediatric Sleep Questionnaire (PSQ) scores. Results: 116 AT and 47 control subjects were recruited, and follow-up data was obtained in 99 AT and 35 control subjects. There were no significant differences between the general (total) HPQ-P scores and subscale scores between the AT and control subjects at entry and there were no significant differences in the change scores (follow-up minus initial scores) between the groups. Regression modeling also demonstrated that there were no group (AT vs control) by time interactions that predicted differential improvements in the HPQ-P ( P  > .10 for each model) although initial PSQ score was a significant predictor of lower HPQ-P scores for all models. Conclusions: Children with SDB experienced improvement in HPQ-P scores postoperatively, but the degree of change was not significant when compared to controls. Further studies incorporating additional educational metrics are encouraged to assess the true scholastic impact of AT in children with SDB.